2004
DOI: 10.1007/s11085-004-7804-x
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation Behavior of an ODS Copper Alloy Cu?Al2O3

Abstract: The oxidation behavior of wt.% Al 2 O 3 ), an ODS copper alloy of interest for aerospace structural application, was investigated by oxidation and two-step oxidation in a TGA. The results were compared with the oxidation kinetics of pure Cu and two other aerospace Cu alloys, and ). AL-15 exhibited the lowest oxidation rate from 500 to 650 • C. The superiority in oxidation resistance is thought to result from the Al 2 O 3 , and the two-step oxidation results suggest the Al 2 O 3 dissolves in the oxide scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Blanching is thought to be caused by oxidation–reduction cycles initiated by fluctuations, caused by hot spots in the geometry or the eventual degradation caused by constant combustion cycling during operation, in the oxygen–hydrogen fuel system. Blanching is represented by surface discolouration and corrosion of the liner wall and has been observed preceding channel wall failure in failed NARloy-Z chambers [19,51,52]. Inspection of blanched regions of NARloy-Z chambers revealed pits, cracks, fissures, and sponge-like appearance which damages the thin-walled coolant channels which roughen and decrease their cooling efficiency [48].…”
Section: Structure Property Correlations Of High-heat-flux Copper Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…Blanching is thought to be caused by oxidation–reduction cycles initiated by fluctuations, caused by hot spots in the geometry or the eventual degradation caused by constant combustion cycling during operation, in the oxygen–hydrogen fuel system. Blanching is represented by surface discolouration and corrosion of the liner wall and has been observed preceding channel wall failure in failed NARloy-Z chambers [19,51,52]. Inspection of blanched regions of NARloy-Z chambers revealed pits, cracks, fissures, and sponge-like appearance which damages the thin-walled coolant channels which roughen and decrease their cooling efficiency [48].…”
Section: Structure Property Correlations Of High-heat-flux Copper Alloysmentioning
confidence: 99%
“…Rocket combustion chamber liners made with NARloy-Z were susceptible to blanching during operation, so extruded GRCop-84’s oxidation behaviour was investigated by Thomas-Ogbuji and Humphrey and compared to NARloy-Z and OFHC Cu with thermogravimetric analysis (TGA), scanning electron microscopy, electron dispersive spectroscopy, and X-ray diffraction [51,101]. They found that the alloys had similar oxidation rates at or above 1023 K, but at intermediate temperatures closer to the operating temperatures between 773 and 1023 K, GRCop-84 exhibited significantly higher oxidation resistance [101].…”
Section: Environmental Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The calcination process is limited (Liang et al, 2004) because the Al 2 O 3 particle size has to be large enough to allow effective milling, while internal oxidation can only produce composites with a low volume fraction of Al 2 O 3 particles, such as oxide dispersion strengthened alloys. Oxidation was used in conjunction with mechanical alloying (Ogbuji, 2004). In this process, Cu-Al alloy powder was milled under an oxidizing atmosphere to produce the composite powder.…”
Section: Nickel-based Composite Powders With Al 2 Omentioning
confidence: 99%
“…Besides sub-and full-scale test programs, a multitude of lab-scale investigations where conducted on the oxidation and blanching related behavior of several copper alloys 5,[13][14][15][16][17][18][19][20][21][22][23] . The majority of these lab-scale investigations were concerned with the comparison of the oxidation behavior of different copper alloys (e.g.…”
Section: Introductionmentioning
confidence: 99%